1999
DOI: 10.1097/00007890-199906270-00010
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Liver Injury and Fatal Alcoholic Hepatitis Occurring After Liver Transplantation in Alcoholic Patients

Abstract: Alcohol-related liver disease (ALD) is a common indication for orthotopic liver transplantation (OLT) in adults. Although return to 'heavy drinking' post-OLT is believed to be uncommon, the prevalence and severity of alcohol-related liver injury in such patients is not well characterized. We retrospectively reviewed the records of 68 adult patients who underwent OLT for ALD to determine the incidence of return to heavy drinking and to assess their clinical outcome. Follow-up ranged from 8-99 months (mean 42) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 17 publications
7
29
0
1
Order By: Relevance
“…Here, recurrent alcohol liver disease was limited to steatosis (42) and was not responsible for progressive fibrosis. These results compare favorably with others: allograft alcoholic hepatitis and cirrhosis after relapse are well described (5,16,43,44), but are uncommon and rarely cited as a significant cause of graft failure (6,27,30). Steatosis affected fewer than 10% of patients after 7 years follow-up, compared with much higher recurrence rates for autoimmune liver diseases or viral hepatitis (15-25% and >50%, respectively), with a proportion of the latter developing cirrhosis by that time.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Here, recurrent alcohol liver disease was limited to steatosis (42) and was not responsible for progressive fibrosis. These results compare favorably with others: allograft alcoholic hepatitis and cirrhosis after relapse are well described (5,16,43,44), but are uncommon and rarely cited as a significant cause of graft failure (6,27,30). Steatosis affected fewer than 10% of patients after 7 years follow-up, compared with much higher recurrence rates for autoimmune liver diseases or viral hepatitis (15-25% and >50%, respectively), with a proportion of the latter developing cirrhosis by that time.…”
Section: Discussionsupporting
confidence: 79%
“…In our cohort, daily ethanol consumption better predicted relapse, perhaps because it better indicates the severity of addiction (37). No explant histological feature in this or another (38) study predicted relapse, unlike with Conjeevaram et a1., who correlated Mallory bodies with relapse (16). The finding of many Mallory bodies in 16% of explants in the Conjeevaram study (16), compared with small foci in 33% explants here, suggest different pretransplant drinking behaviors.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Alcohol recidivism has been reported to impair long-term outcome [24,26,27,[29][30][31] , presumably due to its negative influence on the recipients, including alcohol toxicity, poor compliance, development of post-transplantation malignancies and occurrence of cardiovascular diseases. Rates of graft loss due to alcoholic recidivism range between 0% and 50% [21,27,30,40,41] , and significant association of ALD patients with increased development of post-transplantation malignancy and occurrence of cardiovascular diseases were suggested [1,42] .…”
Section: Patient Outcomesmentioning
confidence: 99%
“…A recent retrospective analysis of 300 patients who underwent OLT for alcoholic liver disease between 1989 and 2002 demonstrated that survival was significantly reduced in subjects who resumed abusive drinking compared with abstinent subjects or subjects with occasional 'slips' (96). Other studies have also shown that recurrent alcoholic liver disease accounts for the majority of deaths among recipients who resumed abusive drinking after transplantation (97,98). Therefore, it is imperative to implement programmes that prevent OLT recipients from further alcohol abuse.…”
Section: Recurrence Of Alcohol-related Liver Disease After Transplantmentioning
confidence: 99%